Wpływ turystyki i agroturystyki na rozwój społeczno-gospodarczy gminy Kamionka Wielka - Pękala, Anna (My University, 2013)
Praca opisuje turystykę i agroturystykę oraz ich wpływ na rozwój społeczno gospodarczy. Opisane zostały pojęcia rozwoju społeczno-gospodarczego i lokalnego oraz instrumenty rozwoju. Badania przeprowadzono w formie ankiety przeprowadzonej wśród mieszkańców gminy i osób spoza niej. Analiza danych z ankiety pozwala na stwierdzenie, iż gmina Kamionka Wielka powinna inwestować w rozwój turystyki i agroturystyki na jej terenie gdyż są one szansą rozwoju społeczno-gospodarczego. W gminie Kamionka Wielka zauważalne są zmiany powstałe pod wpływem turystyki i agroturystyki, mieszkańcy coraz więcej inwestują, powstają nowe przedsiębiorstwa.

This document described the tourism and the agrotourism and their social-economic impact on development. It described the concept of socio-economic development and local development and development instruments. They conducted research in the form of poll conducted amongst residents of the commune and persons from outside commune. The data’s analysis from the questionnaire form lets the statement, that commune of Kamionka Wielka she should invest in the development of tourism and agrotourism on her area because they are a chance of the social-economic development. In the commune of Kamionka Wielka occurring changes are noticeable under the influence of the tourism and the agrotourism, residents more and more are investing, new companies are formed.
The impact of tourism and agrotourism on social-economic development of the community Kamionka Wielka
Keywords: turystyka; agroturystyka; rozwój społeczno-gospodarczy; rozwój lokalny; instrumenty rozwoju; tourism; agrotourism; social-economic development; local development; instruments of development